326 DEFINITIVE CHEMORADIOTHERAPY COMPARED TO NEOADJUVANT CHEMORADIOTHERAPY WITH ESOPHAGECTOMY FOR LOCO-REGIONAL ESOPHAGEAL CANCER: NATIONAL POPULATION-BASED COHORT STUDY. (14th September 2020) - Kamarajah, S; Phillips, A; Hanna, G; Low, D; Markar, S
Abstract:  : Ongoing randomized controlled trials seek to evaluate the potential organ-preservation strategy of definitive chemoradiotherapy as a primary treatment for esophageal cancer. This population-based cohort study aimed to assess survival following definitive chemoradiotherapy (DCR) with or without salvage esophagectomy (SALV) in the treatment of esophageal cancer. Methods: Data from the National Cancer Database (NCDB) from 2004 to 2015, was used to identify patients with non-metastatic esophageal cancer receiving either DCR (n = 5, 977) or neoadjuvant chemoradiotherapy with planned esophagectomy (NCRS) (n = 13, 555). Propensity score matching (PSM) and multivariable analyses were used to account for treatment selection bias. Subset analyses compared patients receiving salvage esophagectomy after DCR (SALV) with NCRS. Results: Comparison of baseline demographics of the unmatched cohort revealed that patients receiving NCRS were younger, had a lower burden of medical comorbidities, lower proportion of squamous cell carcinoma (SCC) and more positive lymph nodes. Following matching, NCRS was associated with significantly improved survival compared with DCR (HR: 0.60, 95% Confidence Interval (CI): 0.57—0.63, p < 0.001), which persisted in subset analyses of patients with adenocarcinoma (HR: 0.60, 95%CI: 0.56—0.63, p < 0.001) and SCC (HR: 0.58, 95%CI: 0.53—0.63, p < 0.001). There was no difference in overall survival between SALV and NCRS (HR: 1.00, 95%CI: 0.90—1.11, p = 1.0). Conclusion: Surgery remains an integral component of the management of patients with esophageal cancer. Neoadjuvant therapy followed by planned esophagectomy appears to remain the optimum curative treatment regime in patients with loco-regional esophageal cancer.